PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI COKRO SUPERTIRTA KLATEN - Aji Mirza Amirul Haque; Burhanudin Ahmad Yani; Sudarwati Sudarwati; Sitti Mukarromah (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to analyze the influence of leadership, work environment and discipline on employee performance at PT. Cokro Supertirta Klaten. Research data obtained from questionnaires with the number of respondents 42 respondents who are employees of PT. Cokro Supertirta Klaten. The research data were analyzed using multiple linear regression analysis. The equation model is processed using the SPSS for windows version 1.6 application. The results showed that the leadership, work environment and work discipline simultaneously had a significant effect on the performance of the employees of PT. Cokro Supertirta Klaten. Leadership, work environment and work discipline simultaneously have a significant effect on employee performance at PT. Cokro Supertirta Klaten. The results of the coefficient of determination can be concluded that the variables of motivation, discipline and work environment provide a positive contribution of 66.1% to the dependent variable, while the remaining 33.9% is influenced by other factors outside the variables studied, such as providing incentives or educational level or factors. other. Keywords : Leadership, work environment, work discipline